The impact of tibolone and hormone therapy on serum C-reactive protein, tumor necrosis factor- and hepatocyte growth factor in postmenopausal women - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2009)
Objective To investigate the effect of tibolone and hormone treatment on serum C-reactive protein, tumor necrosis factor- and hepatocyte growth factor as independent markers of cardiovascular disease. Design Ninety-five normotensive and healthy postmenopausal women with no systemic or cardiac disease who attended the Marmara University Menopause Outpatient Clinic were included in this study. The women were assigned into three groups. The women who accepted hormone replacement therapy were randomized to two groups. Group 1 received 0.625mg conjugated estrogen (CE)+2.5mg medroxyprogesterone acetate (MPA)/day. Group 2 received 2.5mg tibolone/day. Group 3 was the control group consisting of women who did not want hormone replacement therapy. Serum samples were measured for highly specific C-reactive protein, tumor necrosis factor and hepatocyte growth factor before the treatment and after 6 months of therapy. Values at the end of the 6th month and baseline were compared. Results The increase in C-reactive protein and the decrease in tumor necrosis factor- levels demonstrated at the end of treatment were statistically significant, in both the hormone therapy and tibolone groups. However, the decrease in hepatocyte growth factor was significant only in the tibolone group. Conclusions The positive impact of both tibolone and hormone therapy on inflammatory markers appears to be protective against cardiovascular diseases. However, the clinical implications of these findings are yet to be evaluated in large clinical trials.
Keywords: Tibolone; Hormone Treatment; Inflammatory Markers; ESTROGEN PLUS PROGESTIN; REPLACEMENT THERAPY; CARDIOVASCULAR-DISEASE; INFLAMMATORY MARKERS; HEART-DISEASE; FACTOR-ALPHA; RISK; 17-BETA-ESTRADIOL; INTERLEUKIN-6; ELEVATION